“Effects of PAD, DAU, DAK, and SiLPA Capital Expenditure: Economic Growth Moderation in North Sumatra” - Nengsyh Untari Panjaitan; Abdillah Arif Nasution; Khaira Amalia Fachrudin (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effect of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Budget Financing Surplus (SiLPA) on Capital Expenditure with Economic Growth as a moderating variable in regencies/cities. This research employed a quantitative approach using secondary data obtained from regional government budget realization reports and related official publications during the research period. The analytical method used in this study was panel data regression with moderation testing through Moderated Regression Analysis (MRA). The results indicate that PAD, DAU, DAK, and Economic Growth do not have a significant effect on Capital Expenditure, while SiLPA has a significant effect on Capital Expenditure. Furthermore, Economic Growth is unable to moderate the relationship between PAD and DAK on Capital Expenditure, but it is able to moderate the relationship between DAU and SiLPA on Capital Expenditure. These findings indicate that the allocation of regional Capital Expenditure has not been fully influenced by regional fiscal capacity and economic growth, but is also affected by regional budget policy priorities which still tend to focus on routine and operational expenditures. This study is expected to contribute to the development of regional financial studies and serve as a consideration for local governments in improving budget management effectiveness to support sustainable regional development.